Railway Union delegates, TUC Congress, Bournemouth, 1926
1926-09-30 "Railway Union delegates, TUC Congress, Bournemouth, 1926" [g0939001.jpg], September 1926 Delegates from the National Union of Railwaymen - (l-r) C.T. Cramp (General Secretary), W. Dobbie, J. Marchbank and J. Grierson. TUC Organisation